1986
DOI: 10.1007/bf01966206
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic efficacy of inhibitors of human phospholipase A2 in septic shock

Abstract: Soluble phospholipase A2 has been implicated in the pathogenesis of local and systemic inflammatory reactions. Elevated levels of circulating phospholipase A2 (PLA2) correlate with the severity of circulatory collapse and pulmonary dysfunction in gram-negative septic shock. Characterization of septic shock serum PLA2 revealed a calcium-dependent enzyme with absolute 2-acyl specificity with a pH optimum of 7.5. We tested a number of therapeutic agents for their ability to inhibit PLA2 from human septic shock se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

1988
1988
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 34 publications
1
22
0
3
Order By: Relevance
“…As antag onism of IL-1 increases survival after lethal endotoxemia in mice [7], interference wilh the production of this cytokine may contribute to the effects observed. Chlorpromazine has a wide range of pharmacologic activities, from antipsychotic and antihistaminic actions [32] to inhibition of phospholipase A2 [33]. To what extent these activities contribute to the effects in lethal endotoxemia is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…As antag onism of IL-1 increases survival after lethal endotoxemia in mice [7], interference wilh the production of this cytokine may contribute to the effects observed. Chlorpromazine has a wide range of pharmacologic activities, from antipsychotic and antihistaminic actions [32] to inhibition of phospholipase A2 [33]. To what extent these activities contribute to the effects in lethal endotoxemia is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…Among PLA 2 s, a 85-kDa cytoplasmic PLA 2 (cPLA 2 ) is known to play a critical role in the pathogenesis and progression of inflammation, including endotoxic shock. The protective effects of PLA 2 inhibitors in endotoxic shock (10,11), or reduced septic symptoms in PLA 2 -deficient mice (12,13), indicate that PLA 2 is an essential component in the pathogenesis of endotoxic shock. We have previously shown that Gln protects animals from endotoxic shock through its inhibition of cPLA 2 activity (14), and this activity of Gln was also associated with suppression of asthma in mice (15).…”
mentioning
confidence: 99%
“…CPZ has a wide range of pharmacological activities, such as the anti-psychotic and anti-histaminic actions and the phospholipase A2-inhibitory properties [1,11]. This protective effect has been associated with more specific inhibition of TNF, unlike DEX [7].…”
mentioning
confidence: 99%